Narrativas de consumo e cotidianidade: o discurso verde presente em embalagens e suas apropriações por mulheres de diferentes gerações - Vollmer, Lara Cristina (2013)
The discourse surrounding sustainability appears in the means of communication like a powerful tool of persuasion in favor of consumption. The choice of products and services has brought with it, now more than ever, ethical, cultural, environmental, social and political implications. Within this scenario, this study seeks to understand the questions relative to green discourse, sustainability and the different forms of reflexivity of modern life, whose social practices are constantly examined and reformulated in light of information, as proposed by Giddens (1991). The study seeks to promote reflection on the circulation of green discourse and its appropriations by women of different generations, using an exploratory referential product packaging, which today acts as a strong vehicle of consumer communication and mobilization. It also seeks to better understand the relations between these generations and the topic proposed, locating convergence and divergence, points of conflict, reflexivity, fault and trust, and other aspects. To achieve this, we will use oral reports, narratives of consumption and analysis of discourse as empirical research methods, as well as on location observations of semi-structured interviews as methodological techniques, which will allow us to follow a temporal and textual path through the culture and social memory of these different generations. We will attempt to problematize the intersections between discourse an practice that emerge from the everyday experiences of these people, which will allow us to engage in a more in-depth reflection on the social uses of packaging as support for the promotion of education and civic engagement.